BIBLIOMETRIC ANALYSIS AS A BASIS FOR RESEARCH ON SUSTAINABILITY IN TOURISM IN BOSNIA AND HERZEGOVINA - Andrijana Mrkaić Ateljević (Collection of Papers New Economy, 2025)
This work is focused on easier understanding of the ambitions of sustainable tourism. The research was conducted through two contexts. The first is the analysis of scientific literature with the aim of establishing indicators that were used in the quantitative part of the research, which represents the second context of the work. A wide systematic review of the literature provided ideas for the construction of indicators from the three dimensions of sustainability, on the basis of which a composite index of sustainability was later established. This index is a useful tool that enables combining multiple indicators into a single, synthetic measure. The goal of the overall research is to create a more innovative approach to the analysis of sustainable tourism, while respecting the importance of previous scientific works. The results of the regression analysis point to the controlled impacts of tourism, but in the short term, given that an increase in tourist arrivals would lead to an increase in the composite index. However, increasing the average length of stay would reduce sustainability. The purpose of the work is to contribute to future research in the field of sustainable tourism, the guidelines of which are set by the results of the analysis.